2007
DOI: 10.1111/j.1600-079x.2007.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of melatonin receptors and inhibitory effect of melatonin on hydrogen peroxide‐induced endothelial nitric oxide synthase expression in bovine cerebral blood vessels

Abstract: Melatonin plays a key role in a variety of important physiological functions including influencing cerebral blood vessels. Therefore, in the present study, we have identified the existence of melatonin receptors and test the effect of melatonin on hydrogen peroxide-induced endothelial nitric oxide synthase (eNOS) expression in bovine cerebral arteries. The results indicate that mt1A melatonin receptor mRNA is expressed in bovine cerebral arteries. The relative levels of mt1A melatonin receptor mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…C). The increase of mitochondrial PC in SOD2 −/+ mice is consistent with the proposed antioxidant role of SOD2 (Williams et al, ; Miao and St. Clair, ), whereas the increase of mitochondrial 3‐NT levels in TgSOD2 mice could result from the well‐known ability of SOD2‐derived H 2 O 2 to induce NOS and thus NO production (Shimizu et al, ; Ha et al, ; Chucharoen et al, ). Although the observation that no changes with regard to PC or protein‐bound HNE levels were found in the whole‐brain homogenate obtained from both SOD2 −/+ and TgSOD2 mice is in agreement with a previous work (Ibrahim et al, ), it remains to be understood why a reduction of 3‐NT levels has been observed.…”
Section: Discussionsupporting
confidence: 71%
“…C). The increase of mitochondrial PC in SOD2 −/+ mice is consistent with the proposed antioxidant role of SOD2 (Williams et al, ; Miao and St. Clair, ), whereas the increase of mitochondrial 3‐NT levels in TgSOD2 mice could result from the well‐known ability of SOD2‐derived H 2 O 2 to induce NOS and thus NO production (Shimizu et al, ; Ha et al, ; Chucharoen et al, ). Although the observation that no changes with regard to PC or protein‐bound HNE levels were found in the whole‐brain homogenate obtained from both SOD2 −/+ and TgSOD2 mice is in agreement with a previous work (Ibrahim et al, ), it remains to be understood why a reduction of 3‐NT levels has been observed.…”
Section: Discussionsupporting
confidence: 71%
“… showed direct, MT1R‐ and MT2R‐independent vasodilator effects of melatonin in fetal cerebral arteries, which might be related with a local sympathetic‐inhibitory mechanism, able to diminish norepinephrine‐induced contraction. In this sense, at least MT1R is highly expressed in bovine MCA . Although we did not quantify expression or activity of MT receptors, in our model, melatonin might be acting by both MTR‐dependent and independent pathways.…”
Section: Discussionmentioning
confidence: 95%
“…In mammals, numerous physiological roles of melatonin are mediated via activation of two high-affinity G protein-coupled receptors, MT1 and MT2 28 , 29 , which are expressed both singly and together in various tissues with different expression profiles 30 32 . Regarding the mediation of melatonin functions, MT1 and MT2 receptors appear to vary among different tissues and cell types, and even within the same cell type 29 , 33 .…”
Section: Introductionmentioning
confidence: 99%